Advances in lipid carriers for drug delivery to the gastrointestinal tract. (April 2021) - Xu, Yining; Michalowski, Cecilia Bohns; Beloqui, Ana
Abstract: Lipid-based formulations have re-emerged as oral drug delivery systems. Advances in the techniques to evaluate the in vivo fate of the formulations, together with an improved knowledge of the gastrointestinal processes/barriers to the evolving lipid-based systems, could explain, at least partially, this revival. In addition, the use of lipid-based formulations is no longer limited to highly lipophilic drugs and has been extended to hydrophilic peptides and macromolecules. Last but not least, (targeted) nanocarriers have been developed exploiting gut physiology toward novel targets in the field. We herein review what we believe have been the major advances in oral drug delivery via lipid-based formulations in recent years, leading to their re-emergence as promising drug delivery systems for future clinical application. Graphical abstract: Image 1